(untitled) (Applied Biological Research, 2022)
Canine Parvovirus strains 2a, 2b, and 2c cause myocarditis and acute hemorrhagic gastroenteritis in dogs (Goddard and Leisewitz, 2010). Severe clinical condition mostly affects puppies of < 6 months ages while adult dogs with immunological deficiencies are also at danger (Mylokanis et al., 2016). The enteritis variant of myocarditis is less prevalent than the myocarditis form. This type of infection causes peracute mortality due to the heart failure in puppies infected during prenatal life or in infants younger than 8 weeks age whose moms are not vaccinated. Cardiac biomarkers are used as useful indicators for heart disease diagnosis. Such biomarkers include cardiac troponins (cTnI, cTnT), creatine kinase myocardial band (CK-MB), and brain natriuretic peptide (BNP) (Er and Ok, 2015). Cardiac troponins are reliable indicators of cardiac damage, and even minor elevations in these markers are significant in myocardial injury. In dogs with parvoviral enteritis large increases in blood CK-MB and BNP levels, as well as a modest rise in cTnI levels have been reported. Moreover, the evidences of hypercoagulability without disseminated intravascular coagulo pathy have been documented in puppies with CPV enteritis (Otto et al., 2000). In puppies with CPV enteritis, hypercoagulability without disseminated intravascular coagulopathy has been observed (Otto et al., 2000). Robinson et al. (1979) have reported that viral myocarditis suspected puppies had small R waves, S-T segment elevation, QRS notching and paroxysmal ventricular tachycardia. Only very young cardiac muscle fiber (in puppies of <8 weeks age) was found susceptible to fatal parvoviral infection and had smaller R wave, ST segment elevation and QRS notching (Carpenter et al., 1980). The aim of this study was to assess the changes in some selected cardiac biomarker such as cTnI, ECG changes and coagulation profiles in parvoviral enteritis and present the importance of these parameters for prognosis of the disease. Further, the study aimed to determine the presence of myocarditis in enteritis form of disease via cardiac biomarkers.